The Correlation Between the Serum Serglycin Level and the Burden of Coronary Artery Disease in Subjects with Non-St-Elevation Myocardial Infarction - ULUTAS, Zeynep; BOLAYIR, Hasan Ata (Cardiology and Cardiovascular Medicine, 2020)
Background: Despite the fact that serglycin takes a crucial part in the inflammatory status, the correlation between the coronary artery disease (CAD) severity in subjects having non-ST segment elevation myocardial infarction (NSTEMI) and serglycin is still unknown. Methods: A total of 129 participants, including 90 NSTEMI subjects and 39 healthy controls, were included in the present research prospectively. The patient group was separated into two groups as subjects with a high SYNTAX score, which was equal to or higher than 32 (40 subjects), and subjects with a low SYNTAX score, which was lower than 32 (50 subjects). The enzyme-linked immunosorbent assay test was utilized to measure serglycin level from the collected blood serum samples. Results: A considerably higher serum serglycin level (17.2±3.4 ng/mL) was determined in NSTEMI subjects having the high SYNTAX score in comparison with NSTEMI subjects having the low SYNTAX score (11.4±2.1 ng/mL) and the control group (7.9±2.7 ng/mL). The serglycin cut-off value to predict the high SYNTAX score as a result of receiver-operating characteristic curve analysis was identified as 14.8 ng/mL, with a sensitivity of 67% and a specificity of 58%. Serglycin independently predicted the high SYNTAX score with an odds ratio of 0.999, a confidence interval of 95% (0.998–1.000), and p=0.007. Conclusion: Serglycin may represent a possible blood sample value in order to predict the CAD severity in NSTEMI subjects.